The Ethical Responsibility Of Lawyers In The Dissemination Of False Information And Its Implications For The Image Of The Legal Profession - Machmud, Amir; Bustaman, Bustaman (JURNAL HUKUM SEHASEN, 2025)
The spread of fake news by advocates has become an important issue in the digital era that can damage the image of the legal profession. This study aims to identify the ethical and legal responsibilities that advocates must adhere to and analyze the impact of fake news dissemination on the profession's image. The method used is a normative legal approach, analyzing applicable codes of ethics and regulations. The analysis results show that non-compliance with ethical codes can lead to disciplinary sanctions and negative stigma against the legal profession. This study recommends the need for ongoing education, transparency, and responsible use of technology by advocates, as well as strengthening reporting mechanisms by professional associations. With a commitment to ethics, advocates can enhance public trust in the legal system.